Does renin angiotensin system blockade deserve preferred status over other anti-hypertensive medications for the treatment of people with diabetes? - Barzilay, Joshua I.; Whelton, Paul K.; Davis, Barry R. (Annals of Translational Medicine; Vol 4, No 10 (May 25, 2016): Annals of Translational Medicine (Focus on “State of the Art in Diagnostics of the Acute Coronary Syndrome”), 2016)
For more than 20 years it has been “accepted medical dogma” that patients with diabetes mellitus (DM) and hypertension, renal disease, or cardiovascular disease (CVD) should be treated with an angiotensin converting enzyme inhibitor (ACEi) or an angiotensin II receptor blocker (ARB) that blocks the renin angiotensin system (RAS) (1). So widely held is this belief that RAS blockers are commonly prescribed to individuals with DM who do not have a diabetes-related illness because of their perceived “protective” effects. Recently, several studies and meta-analyses have questioned this practice and have reported that RAS blocking agents do not offer any advantages compared to other antihypertensive medications for the treatment of adults with DM. The most recent such study was published by Bangalore et al. in the February 11, 2016 issue of the BMJ (2).